أثر التصميم الداخلي التفاعلي على فراغ الإستقبال بالفندق الصحي - شمس، على عبدالمنعم على; جودة، دعاء عبدالرحمن محمد; مختار، خالد; حلمي، ضحى عنتر (المؤسسة العربية لإدارة المعرفة, 2022)
أصبح انتشار السياحة الصحية والحرص على تعلم أساليب قيادة حياة صحية أكثر توازناً أمر يجذب الأنظار لوجود الكثير من الفنادق الصحية التي تجمع بين الصحة وكل ما هو متطور في عالم التكنولوجيا التفاعلية. وتكمن مشكلة البحث حول التصميم الداخلي التفاعلي للمناطق الصحية غير مرضي لرغبة المصممين في مواكبه العصر، ويهدف البحث إلى معرفة وحصر أساليب التصميم الداخلي التفاعلي وإيجاد معايير جديدة في معالجة الفراغات الداخلية الوظيفية للأنشطة المختلفة بالفندق الصحي مع توضيح أثارها بما يواكب التطور الحضاري المعاصر، ويتبع البحث المنهج الوصفي التحليلي والمنهج الاستقرائي حول جمع المعلومات وإبراز أنماط تطبيقات التصميم الداخلي التفاعلي في العالم، وكانت من النتائج أن التقنيات التفاعلية استطاعت أن تغير مفهوم النزيل وخبرته عن المعنى التقليدي للفندق الصحي كما حل الكثير من المشاكل التصميم الداخلي للفندق وخلق فراغ داخلي تفاعلي قادر على تلبية احتياجاته في جو من الإبهار والرفاهية والراحة دون الالتفات لعنصر الوقت. The spread of health tourism and the eagerness to learn methods of leading a more healthy life a balance is something that attracts attention, as there are many healthy hotels that combine health and everything that is developed in the world of interactive technology. The problem of the research about the interactive income design for health areas is not satisfactory to the designers’ desire to keep pace with the times, and the research aims to know and limit the methods of interactive interior design in addressing the functional interior spaces of the various activities in the health hotel with an explanation of its effects in line with contemporary civilized development, and the research follows the descriptive analytical approach And the inductive approach about collecting information and highlighting the patterns of interactive interior design applications in the world, and one of the results was that interactive technologies were able to change the guest’s concept and experience from the traditional meaning of the health hotel, as well as solving many problems of the hotel’s interior design and creating an interactive interior space capable of meeting his needs in an atmosphere of dazzling And luxury and comfort without paying attention to the element of time.
Keywords: الفنون التشكيلية -- التصميم الداخلي -- الفندق الصحي -- السياحة الصحية